Kualitas Hidup Orang Tua dengan Anak Developmental Disability - Dewi, Nursetiawati; Mu’in, Muhammad (Jurnal Keperawatan Komunitas, 2015)
Children with Developmental disability is one of vulnerable agrregates who tend to experience health problem caused by their condition. This make they need more help from their parent as a care giver compared to other children. Their dependency lead to complex problem faced by the parent which can lowering their quality of life. Aim of the study was to identify quality of life among parent with developmental disability children. Research method was quantitative with cross sectional approach. Subject of the study were parent who has 2-19 years child with developmental disability and stay in a same home. Instrument used to measure quality of life was WHOQOL-BREF. Data analysis were univariate to describe frequencies of subject characteristic and quality of life. The result showed mean of quality of life in physical, psychological, social, and environmental among parent with deaf/ hearing impairment children was 20.13, 19.2, 9.73, 24; mentally retarded was 19.42, 17.46, 9.19, 22; and Thalasemia was 21, 19.22, 9.44, 24.24. Parent with developmental disability children need to maintain their quality of life used their resources and support.